2021
DOI: 10.3390/ijerph18137070
|View full text |Cite
|
Sign up to set email alerts
|

“If It Goes Horribly Wrong the Whole World Descends on You”: The Influence of Fear, Vulnerability, and Powerlessness on Police Officers’ Response to Victims of Head Injury in Domestic Violence

Abstract: Domestic violence (DV) victims face significant barriers to accessing healthcare. This is particularly concerning in cases of brain injury (BI), which is difficult to diagnose and risks severe long-term consequences for DV victims. Police may be able to identify head injury (HI) and signpost victims to healthcare. This research investigated potential barriers to police supporting victim health needs by exploring police attitudes towards DV and considering how police interpret and respond to stories of HI in DV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…In our culture, pursuing legal action may carry a social stigma and result in shame or ostracism for the victim and their family. If the victim anticipate reaction from the criminal or their associates, they may be not willing to seek legal help, especially if the victim and their family feel vulnerable and at risk 26 .…”
Section: Discussionmentioning
confidence: 99%
“…In our culture, pursuing legal action may carry a social stigma and result in shame or ostracism for the victim and their family. If the victim anticipate reaction from the criminal or their associates, they may be not willing to seek legal help, especially if the victim and their family feel vulnerable and at risk 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Even in instances in which police officers identify that an individual may have a brain injury, it has been found that they are unlikely to intervene. Officers have said this is because they feel as though they are undereducated and underequipped to deal with these situations, making them afraid they will do more harm than good if they intervene [ 32 ].…”
Section: Diagnosis Of Tbi Secondary To Domestic Violencementioning
confidence: 99%